Testing the Feasibility and Acceptability of a Religiously-Tailored Text Messaging Intervention to Reduce Smoking Among Somali Muslim Men During Ramadan. Issue 8 (5th December 2020) - Pratt, Rebekah; Ojo-Fati, Olamide; DuBois, Diana; Okuyemi, Kolawole; Graham, Amanda L; Mohamed, Sharif; Janowiec, Mark; Kahin, Abdillahi; Mahamud, Abdirahman; Tessier, Katelyn M; Busch, Andrew M; Joseph, Anne M
Abstract: Introduction: The prevalence of smoking among Somali Muslim male immigrants residing in Minnesota is estimated at 44%, however smoking reduction is common during the month of Ramadan. This study evaluated the feasibility and impact of a religiously tailored text message intervention delivered during Ramadan to encourage smoking reduction among Somali Muslim men who smoke. Methods: Fifty Somali men were recruited. Participants received two text messages per day starting 1 week prior to and throughout the month of Ramadan. Approximately half were religiously tailored and half were about the risks of smoking and benefits of quitting. Smoking behavior was assessed at baseline, and at weeks 4 (end of Ramadan), 8, and 16. Outcomes included feasibility, acceptability, and preliminary impact of the text message intervention on smoking reduction and bioverified abstinence. Results: The average age was 41 years. Average time to first cigarette was 1.8 hours at baseline, and 46% of participants smoked menthol cigarettes. Eighteen of 50 participants selected English and 32 selected Somali text messages. Subjects significantly reduced self-reported cigarettes per day (CPD) from 12.4 CPD at baseline to 5.8 CPD at week 16 ( p < 0.001). Seven subjects reported quitting at week 16, five completed CO testing, confirming self-reported abstinence. The majority of participants found the cultural and religious references encouraging at the end of the week 16 survey. Conclusions: Religiously tailored text messages to decrease smoking are feasible and acceptable to Somali Muslim men who smoke during Ramadan. This intervention for addressing smoking disparities is worthy of further study. Implications: Recruitment of Somali Muslim men who smoke is feasible and supports the idea that further studies targeting smoking during Ramadan are practical. Ramadan presents a window of opportunity upon which to build smoking cessation interventions for smokers who identify as Muslim. These preliminary findings suggest that text messaging is a feasible and acceptable intervention strategy, and that religious tailoring was well received. Such an approach may offer potential for addressing smoking disparities among Somali Muslim male smokers. Trial Registration: ClinicalTrial.gov: NCT03379142